Implementacija avtomatiziranega testnega sistema testiranja pirogenosti v bolnišnični proizvodnji parenteralnih raztopin - Tršan, Mateja (Farmacevtski vestnik, 2016)
Production of parental solutions from the hospital's point of view means a scientific and professional challenge. The demand for the in-house parenteral products is high and requires a fast or even immediate response. These products have lower stability and shorter shelf life compared to industrial products. The products must comply with all pharmacopoeian standards. That can only be performed in the production process, which ensures sterility and apyrogenicity of the final parenteral products. However, it is achievable with validated, welldesigned, and constantly controlled production process only. These processes must fully implement the principles of good manufacturing practices. In this regard, we have implemented and validated rapid point-of-use test system that provides quantitative results within 15 minutes. The test system (PTS) utilizes disposable cartridges that are pre-loaded with reagents and a portable and handheld reader to provide quantitative endotoxin amounts. Because of its portability, the PTS allows the testing to be performed at the point of sample collection.
Keywords: (a)pirogenost; bakterijski endotoksini; endotoksinska meja; kvantitativne analize; parenteralne raztopine